SUGGESTED GUIDELINES FOR DESIGN AND CONSTRUCTION OF SHORT—SPAN BRIDGE ABUTMENTS WITH REINFORCED EARTH SYSTEM - Dwindu Agung Gumelar; Indrasurya Budisatria Mochtar (Institut Teknologi Sepuluh Nopember, 2021)
Construction of small bridges is one of the real challenges in road construction, because it has so many problems. The reinforced earth system (mechanically stabilized earth wall) using gabion can be suggested as better alternatives for foundation of short—span bridges, especially in the remote areas. The latest research was about to find the design of reinforced earth abutment on various heights of abutments and various lengths of bridge span on soft to very soft consistency cohesive soil. However, the results of this research were less representative because the field conditions can vary from very soft to stiff cohesive soil and very loose to dense non-cohesive soil. Therefore, further research for wide range of soil conditions was conducted. Based on internal and external stability analysis, known that the number of geotextile needed for MSE wall (reinforced earth structure) ranging from 2 to 5 layer per meter depth, depending on the grade and the depth placed of the reinforcement, while the length of geotextile needed ranging from 3.2 to 22.5 meter, depending on the bridge span, embankment height, and parameters of the soil. MSE Wall cannot be built on soft to very soft soil (Cu < 2.79 Ton/m2) without soil improvement to be done in the first place. Based on circular failure analysis (overall stability), known that in cohesive soils with stiff consistency (Cu = 6 Ton/m2) to very stiff (Cu = 12 Ton/m2) and non-cohesive soils with dense consistency (ф = 380) to very dense (ф = 420) does not require additional reinforcement. While on other soil consistency, some need additional reinforcement ranging from 0 to 22 layer of geotextile and from 0 to 35 pieces of micropiles, depending on the bridge span, embankment height, and grade of the reinforcement. Number of gabion needed as a facing of MSE wall ranging from 5 to 8 pieces per 2-meter width of abutments, depending on the embankment height.